THREATS AND TRUSTED COUNTERMEASURES USING A SECURITY PROTOCOL IN THE AGENT SPACE - Nouh, Sayed; Admassu, Tinbit (Zede Journal of Ethiopian Engineers and Architects, 2023)
Mobile Agent computing is a paradigm of distributed computing, that has generated considerable excitement in the research community. Despite that, it has not been translated into a significant number of real-world applications due to a new dimensionality of security problem it brings along with it. In this paper familiarization to Mobile Agent technology and threat of hostile host towards a visiting agent is given due diligence: Malicious host problem. The threats are identified and a modified mobile computing model is proposed to prevent some of the threats. A prototype that realizes the concept is implemented using IBM’s Mobile Agent platform, Aglets.